2003
DOI: 10.1139/f03-067
|View full text |Cite
|
Sign up to set email alerts
|

Recruitment dynamics of walleyes (Stizostedion vitreum) in Kansas reservoirs: generalities with natural systems and effects of a centrarchid predator

Abstract: Knowledge of factors influencing recruitment dynamics of walleyes (Stizostedion vitreum) in different systems and regions is important for developing a better understanding of walleye ecology. Therefore, we investigated associations among walleye recruitment and climatic, water-level, and biotic characteristics in four Kansas reservoirs during 1985–1999. Walleye recruitment was positively related to spring storage ratios and temperatures and negatively associated with spring water levels and abundance of 130- … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
78
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(83 citation statements)
references
References 29 publications
(41 reference statements)
5
78
0
Order By: Relevance
“…Similar to macroinvertebrate densities on the UMRS, many biotic components in diverse aquatic ecosystems exhibit high temporal variability (Gido et al 1997;Bunn and Davies 2000;Dunham et al 2002;Quist et al 2003). Much of the year-to-year variability seen in the target taxa collected by the LTRMP is actual change and not error variance.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to macroinvertebrate densities on the UMRS, many biotic components in diverse aquatic ecosystems exhibit high temporal variability (Gido et al 1997;Bunn and Davies 2000;Dunham et al 2002;Quist et al 2003). Much of the year-to-year variability seen in the target taxa collected by the LTRMP is actual change and not error variance.…”
Section: Discussionmentioning
confidence: 99%
“…Once fish have passed through this step, invasiveness (at least in terms of geographic spread) may ultimately rely on a secondary set of criteria including biotic interactions and life-history variables. The intriguing combination of high abiotic tolerance and low invasiveness in T. vittata may support the biotic-abiotic constraining hypothesis (Quist et al 2003), wherein abiotic environmental variables structure population levels until overridden by biotic ones (e.g., predation, competition). For example, Quist et al (2003) showed that variation in walleye Stizostedion vitreum (now Sander vitreus [Mitchill, 1818]) populations in Kansas reservoirs could be explained by environmental variables until a critical threshold for biotic interactions was reached.…”
Section: Discussionmentioning
confidence: 76%
“…The intriguing combination of high abiotic tolerance and low invasiveness in T. vittata may support the biotic-abiotic constraining hypothesis (Quist et al 2003), wherein abiotic environmental variables structure population levels until overridden by biotic ones (e.g., predation, competition). For example, Quist et al (2003) showed that variation in walleye Stizostedion vitreum (now Sander vitreus [Mitchill, 1818]) populations in Kansas reservoirs could be explained by environmental variables until a critical threshold for biotic interactions was reached. In that case, once the density of a predator (Pomoxis annularis Rafinesque, 1818) was exceeded, then biotic interactions overrode abiotic influences and S. vitreum population dynamics were related to P. annularis density.…”
Section: Discussionmentioning
confidence: 76%
“…The number of larval fish present in a given area can vary dramatically (Cole and MacMillan 1984;Weaver et al 1997;Quist et al 2003;Roseman et al 2005). Thus, rather than compare relative abundances, we decided to use a presenceÀabsence-based approach (sensu Strayer 1999; Royle and Nichols 2003), a well-documented approach in studies of terrestrial organisms.…”
Section: Data Analysesmentioning
confidence: 99%
“…Reservoirs can be variable and dynamic ecosystems and management of water levels in reservoirs is typically guided by hydrological and economic factors (e.g., flood control, hydropower generation, and irrigation), with little consideration given to biotic organisms (Sammons et al 1999;Sammons and Bettoli 2000). For example, some reservoirs experience unpredictable and extreme water-level fluctuations (June 1977;Quist et al 2003;Olds et al 2011) that can be detrimental to the survival of zooplankton and larval fish (Carline 1986;Willis 1986;Naselli-Flores and Barone 1997).…”
Section: Introductionmentioning
confidence: 99%